2004
DOI: 10.1023/b:nere.0000013753.22615.59
|View full text |Cite
|
Sign up to set email alerts
|

Creatine-Enhanced Diet Alters Levels of Lactate and Free Fatty Acids After Experimental Brain Injury

Abstract: Free fatty acids (FFA) and lactic acid are markers of secondary cellular injury following traumatic brain injury (TBI). We previously showed that animals fed a creatine (Cr)-enriched diet are afforded neuroprotection following TBI. To further characterize the neuroprotective Cr diet, we studied neurochemical changes in cortex and hippocampus following a moderate injury. Adult rats were fed either a control or Cr-supplemented diet (0.5%, 1%) for 2 weeks before TBI. At 30 min or 6 h after injury, tissue was proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 54 publications
0
34
0
3
Order By: Relevance
“…Increasing evidence has demonstrated that creatine affords neuroprotection (Wilken et al, 1998;Sullivan et al, 2000;Zhang et al, 2003;Scheff and Dhillon, 2004). The mechanisms implicated in creatine neuroprotection are controversial but they appear to depend on an increase in cellular phosphocreatine stores (Brustovetsky et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that creatine affords neuroprotection (Wilken et al, 1998;Sullivan et al, 2000;Zhang et al, 2003;Scheff and Dhillon, 2004). The mechanisms implicated in creatine neuroprotection are controversial but they appear to depend on an increase in cellular phosphocreatine stores (Brustovetsky et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, creatine pretreatment was the only strategy that had a significantly beneficial cortical tissue sparing compared with injured animals on a standard diet, which duplicated our previously published monotherapy findings. 71,73 Further, the combination therapy did not improve tissue sparing over creatine monotherapy.…”
Section: Concurrent Targeted Therapy Combination: Glypromate and Minomentioning
confidence: 94%
“…Impairments in mitochondrial ATP biosynthesis seen after TBI can be partially offset by providing a diet high in creatine as a pre-treatment. 68,70 Indeed, dietary creatine supplementation as a mono-agent pre-injury treatment has been shown to afford significant neuroprotection in animal models of TBI [71][72][73] as well as other conditions such as Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, and cerebral ischemia. Increased phosphocreatine availability and ATP synthesis, in conjunction with reduced mitochondrial impairment and improved calcium dynamics, are thought to contribute to the neuroprotective actions of creatine observed in these models.…”
Section: Concurrent Targeted Therapy Combination: Glypromate and Minomentioning
confidence: 99%
“…Moreover, creatine-treated rats displayed significantly increased mitochondrial membrane potentials, levels of mitochondrial calcium and ATP, and significantly decreased levels of reactive oxidative intermediaries, relative to rats not given creatine. In another work, rats fed a diet containing 1% creatine before experiencing controlled cortical contusions had significantly more sparing of cortical tissue and suppressed levels of lactate and free fatty acids than rats not given creatine [43]. Finally, creatine supplementation can also reduce (1) ischemia-mediated depletion of ATP and (2) caspace-3-activation and cytochrome c release, which are indicators of cell damage [44].…”
Section: Traumatic Brain Injurymentioning
confidence: 98%